Induction of Microsomal Liver Enzymes by Silymarin in Experimental Animals - Mshiemish, Bahir A.R.; Hussain, Saad A. R.; Suliman, Amaal A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: previous researches showed that the hepatoprotective effect of silymarin was through inhibition of cytochrome p450- system (e.g. protection against Amanita toxin), in addition to protection from free radicals generated by this enzymatic system. In contrast to that, many evidences clarified that silymarin may increase first pass metabolism of e.g. cyclosporine and benzodiazepenes.Objective: Our aim from this animal experiment was to relieve this confusion and detect that this herbal extract is absolutely hepatoprotective or induce hepatotoxicity in other conditions.Materials and Methods: this study was performed on 15 healthy male rats randomized into two treatment groups; first group (5 rats) pretreated with phenobarbital (I.P) then given acetaminophen (I.P) and the second group (5 rats) pretreated with silymarin (orally) then given acetaminophen (I.P.); while the last five rats were considered as control group for comparison . Activities of SGOT, SGPT and histopathological sections were detected for both groups and compared with that of control.Results: for both treatment groups, the activities of transaminase enzymes were significantly higher than control group. Meanwhile; activity of these enzymes and severity of hepatic damage were significantly higher for Phenobarbital group compared with silymarin.Conclusion: we can conclude from this experimental study that, even though silymarin act as hepatoprotective by multifactorial mechanisms (antioxidant, increase glutathione level, antifibrotic, anti-inflammatory and enzyme inhibitor), it may act as enhancer for some hepatotoxic agents (like acetaminophen) by cytochrome P-450 induction mechanism.